Information aggregation in experimental asset markets in the presence of a manipulator - Veiga, H.; Vorsatz, M. (Experimental Economics, 2010)
We study with the help of a laboratory experiment the conditions under which an uninformed manipulator—a robot trader that unconditionally buys several shares of a common value asset in the beginning of a trading period and unwinds this position later on—is able to induce higher asset prices. We find that the average price is significantly higher in the presence of the manipulator if and only if the asset takes the lowest possible value and insiders receive perfect information about the true value of the asset. It is also evidenced that the robot trader makes trading gains. Finally, both uninformed and partially informed traders may suffer from the presence of the robot.